1996
DOI: 10.1044/1058-0360.0501.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phonological Decoding Training on Children's Word Recognition of CVC, CV, and VC Structures

Abstract: The effects of training in letter-sound correspondences and phonemic decoding (segmenting and blending skills) on three kindergartners' word recognition abilities were examined using a single-subject multiple-baseline design across behaviors and subjects. Whereas CVC pseudowords were trained, generalization to untrained CVC pseudowords, untrained CVC real words, untrained CV and VC pseudowords, and untrained CV and VC real words were assessed. Generalization occurred to all of the untrained constructions for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Their performance is comparable to that of speaking children with similar instruction. 24 Maintenance measures obtained post-instruction for both Gabe and Jane indicated that generalized phonemic awareness knowledge for trained CVC pseudowords had not declined following termination of instruction. Both Gabe and Jane also showed steady progress toward criterion in their generalization of encoding skills to untrained CVC pseudo and real words.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Their performance is comparable to that of speaking children with similar instruction. 24 Maintenance measures obtained post-instruction for both Gabe and Jane indicated that generalized phonemic awareness knowledge for trained CVC pseudowords had not declined following termination of instruction. Both Gabe and Jane also showed steady progress toward criterion in their generalization of encoding skills to untrained CVC pseudo and real words.…”
Section: Discussionmentioning
confidence: 97%
“…24, 33 -34 The CVC syllable structure was used because it is the basic syllable shape for tasks involving segmentation and blending. 24 Pseudowords were chosen because (1) pseudoword decoding is a strong predictor of later reading abilities, 35 -36 and (2) use of pseudowords minimizes the influence of prior learning. The following research questions were posed:…”
Section: Phonological Awareness and Phoneme-grapheme Correspondence Imentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention studies (18,19) showed that stimulation of letter naming and grapheme-phoneme relationship, along with the direct practice of reading of C-V-C monosyllabic non-words, result in the dissemination of trained reading skills for the reading of untrained words and pseudowords of different lengths and syllabic structures. This finding suggests that the program prepared and applied in this study also produced the widespread of the reading skill.…”
Section: Discussionmentioning
confidence: 99%
“…Following the pre-assessment, children at risk for reading disabilities were submitted to the Phonological Decoding Intervention Program developed by the researchers based on two international studies (18,19) . The program was designed to be conducted in two phases: Phase I and Phase II.…”
Section: Thismentioning
confidence: 99%